2012
DOI: 10.1136/bcr-2012-006907
|View full text |Cite
|
Sign up to set email alerts
|

Euforia-induced acute hepatitis in a patient with scleroderma

Abstract: Euforia, a supplement containing a variety of natural ingredients, is widely used as an antioxidant and anti-inflammatory formula. It is not approved by the US Food and Drug Administration and its side effects are unknown. We report a 45-year-old woman with limited systemic sclerosis who presented with jaundice and marked elevation of serum transaminases. One month before, she started taking Euforia juice. A liver biopsy disclosed submassive hepatocellular necrosis with histopathological changes consistent wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Case 12 (Jiménez-Encarnación et al 2012) deals with a 45-year-old woman with hypothyroidism and systemic sclerosis who had hepatitis after taking the preparation Euforia ® . The patient was positive for antinuclear antibodies ANA (1:320), suggesting an autoimmune hepatitis; however, ANA are present in up to 98 % of systemic sclerosis patients (Villalta et al 2012); authors concluded that the mechanism of the liver injury was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Case 12 (Jiménez-Encarnación et al 2012) deals with a 45-year-old woman with hypothyroidism and systemic sclerosis who had hepatitis after taking the preparation Euforia ® . The patient was positive for antinuclear antibodies ANA (1:320), suggesting an autoimmune hepatitis; however, ANA are present in up to 98 % of systemic sclerosis patients (Villalta et al 2012); authors concluded that the mechanism of the liver injury was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A recent toxicity report in 2012 was associated with consumption of Euforia juice that contained NJ along with other natural products. A 45-year old woman, consuming Euforia for one month to treat systemic sclerosis, eventually developed jaundice and presented elevated serum transaminases [74]. She was eventually diagnosed with hepatocellular necrosis and histopathological changes indicated toxic hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Her condition improved 18 months after discontinuing Euforia juice. Exact toxicity mechanisms remain unspecified, but several known hepatotoxic natural products including noni were hypothesized to induce herb-herb interactions [74].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[114] Barbaloin and folate showed pharmacological potential. [115] A. arborescens Mill. extract induces prooxidant-antioxidant equilibrium and cytokine synthesis in rowers.…”
Section: Anti-inflammatorymentioning
confidence: 99%